Peningkatan kemampuan guru dalam menerapkan model pembelajaran kooperatif melalui strategi pembimbingan kolaborasi guru di SD Negeri 3 Putat - Hartiningsih, Tri (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2023)
The purpose of this research is to find out to describe the Teacher Collaborative Guidance Strategy to improve the teacher's ability to apply the cooperative learning model. The population is teachers from class I to grade 6 plus physical education teachers at SDN 3 Putat totaling 7 people. Data analysis techniques using descriptive analysis techniques.  This research was carried out in two cycles each cycle including: planning, implementing, observing and reflecting. The results showed that from each cycle there was an increase. In the pre-cycle the teacher's ability to prepare lesson plans showed an average yield of 59.14% while in the implementation of learning 57.62%. In cycle I the results have changed in the preparation of learning plans 72.7% and 65% of learning implementation. In cycle II it increased to 81% in preparing lesson plans and 71% in implementing learning. The results of this study indicate that the teacher's performance at SDN 3 Putat, Purwodadi District, Grobogan Regency in 2021/2022 in semester II in the preparation and implementation of learning for each cycle has increased. In preparing lesson plans from pre-cycle to Cycle I it increased by 13.56% and from cycle I to cycle II rose 8.30%. In the learning process from pre-cycle to cycle I, it increased by 7.38% and from cycle I to cycle II, it increased by 6%.